2019
DOI: 10.1177/0049124119826152
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Discrimination in Correspondence Studies

Abstract: Correspondence studies are popular tools for assessing discrimination against minorities, for example, in the labor market. Typically, two fake Curriculum Vitae (CVs) are sent to multiple job openings. The CVs are equivalent except for a mark identifying the disadvantaged. While it is straightforward to establish discrimination from minorities’ lower response rates, it is often unclear what its source may be. Discrimination may result as much from employers’ aversion toward a minority, as from perceptions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…With the aim of completing the study of the effect of criminal stigma, additional research has been conducted to analyse the factors that explain the behaviour of recruiters with this same database (Rodríguez-Menés & Rovira, 2019). 14 Having sent CVs with different skills levels allowed us to study the mechanisms described by economic theories of discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of completing the study of the effect of criminal stigma, additional research has been conducted to analyse the factors that explain the behaviour of recruiters with this same database (Rodríguez-Menés & Rovira, 2019). 14 Having sent CVs with different skills levels allowed us to study the mechanisms described by economic theories of discrimination.…”
Section: Discussionmentioning
confidence: 99%
“… 14. Note to this edition : There is a difference in the valid sample used between the present study (601 jobs – 2404 applications) and the study of Rodríguez-Menés & Rovira (2019) (580 jobs – 2320 applications). The difference is due that in the analysis of the second study we used the variable of number of applications per vacancy.…”
mentioning
confidence: 96%
“…In the hierarchy of behavioral psychology research methodology, field studies are considered stronger than laboratory studies. Of field methods, correspondence audit studies, in which the investigator randomizes one or more characteristics of fictitious applicants to test for the effect of those characteristics on some outcome, are thought to provide the most compelling evidence of discrimination [38,39]. Our study, which demonstrated prioritization of URM applicants in radiology residency selection, was the first correspondence audit study to investigate bias in medical education admissions.…”
Section: Challenges To the Iatmentioning
confidence: 98%
“…This thesis is based on the premise that employers are ordinarily interested in knowing about previous convictions of applicants to assess the risk of recidivism (DeWitt et al, 2017) and the skills of job applicants (Rodríguez Menés and Rovira, 2019). However, under this explanation, employers conduct CBCs only when they believe they are legitimized to do so.…”
Section: The Unintended Effects Of New Legislation and The Growth In ...mentioning
confidence: 99%
“…1 This may have unfortunate consequences because, when CBCs are prevalent in the labour market, the chances of being hired are low for people with previous convictions (Bushway, 2004). This is because employers do not always base their hiring decisions on a rational risk assessment when they know that a job applicant has been convicted in the past (Rodríguez Menés and Rovira, 2019; Sugie et al, 2020). Thus, people with convictions often do not even bother pursuing certain employment opportunities because they assume that CBCs will be conducted and their qualifications will not be considered (Harding, 2003; Kurtovic and Rovira, 2017).…”
Section: Introductionmentioning
confidence: 99%